2007
DOI: 10.1007/978-1-59745-529-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Flip-the-Tip

Abstract: A conventional borosilicate glass patch pipette is glued into a plastic jacket, forming the entity of a FlipTip. One or two three-channel modules of recording tip sockets are mounted on a liquid handler platform to take up FlipTips. The tip sockets are connected to preamplifiers (HEKA) and to a suction system. The inner chamber of the tip sockets is filled with intracellular solution (IS), and FlipTips are prefilled with extracellular solution (ES) immediately before use. The FlipTips are then inserted into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Previous studies have found no significant differences in channel kinetics between manual and automated patch clamp system (Li et al, 2017). In addition, we did not find any difference in Kv2.1 kinetics when comparing with data obtained with another automated patch clamp robot (Fejtl et al, 2007) that worked with physiological ICS, ECS, and without the need of SES solution (data not shown). Despite these limitations, the solutions used in this study still contain physiological levels of sodium and potassium concentration to better reflect in vivo ion composition, and not bi-ionic high potassium (K + ) solution as used in many previous studies on potassium channels.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have found no significant differences in channel kinetics between manual and automated patch clamp system (Li et al, 2017). In addition, we did not find any difference in Kv2.1 kinetics when comparing with data obtained with another automated patch clamp robot (Fejtl et al, 2007) that worked with physiological ICS, ECS, and without the need of SES solution (data not shown). Despite these limitations, the solutions used in this study still contain physiological levels of sodium and potassium concentration to better reflect in vivo ion composition, and not bi-ionic high potassium (K + ) solution as used in many previous studies on potassium channels.…”
Section: Discussionsupporting
confidence: 50%
“…121,[125][126][127] The Flyscreen 8500 (FlyIon) uses 'ip-the-tip' technology, an adaption of traditional electrophysiology in which suction pulses applied to a cell inside a glass pipette result in true whole-cell conguration, gigaohm seals and resultant high-quality electrophysiology data. 105,128 This platform is fully automated and requires comparatively low volumes of compound. However, with only six electrodes, throughput is low, 105 making the FlyScreen particularly suited to pharmacological characterisation of venom components in limited supply.…”
Section: Automated Electrophysiology Platformsmentioning
confidence: 99%